Milwaukee Bucks - Graves, Will (2023)
"From humble beginnings to one of the world's most popular sports leagues, the NBA has provided thrills to millions of fans since the 1940s. Inside the NBA tells the story of each NBA team, its origins, its successes and failures, and its all-star players and most popular coaches. This NBA series will get you up to speed on your favorite team with fascinating facts and stats, exciting photographs, and much more"--Back cover.
Reaching new heights -- Bucking for titles -- Best of the Bucks -- Milwaukee moments -- Timeline -- Team facts -- Team trivia -- Glossary -- More information -- Online resources -- Index -- About the author.
Includes bibliographical references (page 47) and index.
Ages 8-12
Keywords: Milwaukee Bucks (Basketball team) -- Juvenile literature; Milwaukee Bucks (Basketball team); Basketball -- Juvenile literature; Professional sports -- Juvenile literature; Sports franchises -- Juvenile literature; Basketball; Professional sports; Sports franchises; Juvenile works